Effects of biochar nanoparticles on seed germination and seedling growth. (January 2020) - Zhang, Kun; Wang, Yaofeng; Mao, Jiefei; Chen, Baoliang
Abstract: As a soil amendment, the prospect of biochar application is excellent. However, environmental risks of biochar need to be investigated for its substantial use. The environmental risks of BNPs need urgent attention because at present little knowledge is available. Therefore, the effects of six types of BNPs on seed germination and growth of rice, tomato and reed seedlings were investigated. The BNPs were collected from biochars derived from two feedstocks (rice straw and wood sawdust) under 300 °C (low-temperature), 500 °C (mid-temperature) and 700 °C (high-temperature). The BNPs collected from high-temperature biochar inhibited seed germination of rice. However, all of the BNPs had a stimulating effect on rice seedling growth that significantly increasing the length of its root and shoot. Furthermore, the BNPs collected from high-temperature biochar and lignin-rich feedstock had an inhibiting effect on reed that dramatically decreased shoot length and biomass. Inhibitory effects of BNPs were caused not only by phenolic compounds on its surface, but also by the blocking effect on epidermal openings resulting in a reduced transfer of nutrients and water. No evidence was found that BNPs would affect the seed gemination and seedling growth of tomato plants. This study indicates that the eco-toxicity of BNPs is a potential environmental risk of biochar. Our findings provide new evidence for the necessity of establishing environmental risk management of biochar. Graphical abstract: Image 1 Highlights: Interparticle charge regulation was used to collect biochar nanoparticles (BNPs). BNPs stimulated the growth of rice, oppositely inhibited the growth of reed. BNPs surface deposited phenolic compounds which caused adverse effect on plant. BNPs originated from lignin-rich biomass performed high environmental risk. Abstract : Biochar nanoparticles displayed negative effects on seed germination and seedling growth caused by phenolic compounds on root surface and a blocking effect on epidermal openings.